Can miRNA be the Missing Link Between Parkinson’s Disease and Pesticides? - gobba, fatma (AUC Knowledge Fountain, 2024)
Parkinson’s disease (PD) is a common neurodegenerative condition that leads to significant morbidity and a decline in the quality of life. It develops as a consequence of the loss of dopaminergic neurons in the substantia nigra pars compacta. Nevertheless, the development of PD is influenced by environmental factors, and the intricate nature of these relationships is further complicated by a multitude of factors, including the genetic backgrounds that are specific to populations and variations in environmental exposures, such as pesticides. Pesticides, consisting of a diverse family of chemicals commonly used in both agricultural and household settings to protect crops against insects and fungus, have been identified as potentially notable risk factors for the onset of PD. Therefore, the aim of this study was to compare the expression profiles of a new set of candidate miRNAs associated with the pathogenesis of PD and environmental exposure. The study focused on examining the expression of s hsa-miR34c-5p, hsa -miR132-3p, hsa -miR-7-5p, hsa- miR-181a-5p, hsa -miR-29c,3p, hsa-miR-155-5p, and hsa-miR-17-5p in peripheral blood mononuclear cells (PBMCs) derived from Egyptian patients with PD and comparing them with a reference control group. Furthermore, the analysis extends to include the examination of miRNA expression in both the mild and severe stages of PD patients, along with reference controls, to ascertain whether there is a correlation between miRNA expression and the severity of the disease. Additionally, an exploratory investigation has been conducted to investigate the role of these candidate miRNAs in the early events of PD by comparing the expression profiles of early-onset and normal-onset PD patients with the reference group. A consensus-based strategy has also been proposed to analyze the data on miRNA expression to gain a more profound understanding of the molecular regulatory changes that occur during Parkinson’s disease. The levels of miRNA expression in PBMCs obtained from 50 patients with PD and 39 control subjects were evaluated using the reverse transcription-quantitative real-time PCR method. The study also assessed the ability of these expression levels to distinguish between patients with Parkinson’s disease and reference individuals by ROC curve analysis. A dysregulated miRNA-based network was constructed in PD using an approach that involved consensus, integration, and identification of respective targets and transcription factors. In addition, enrichment analysis was performed to obtain the enriched gene ontology and pathways. Our results demonstrated significant downregulation of hsa-miR-34c, miR-132, miR-7, and miR-29c and overexpression of hsa- miR-181a and miR-155. On the other hand, miR-17-5p did not show any significant differences. Nevertheless, the level of expression of miR-17 showed significant upregulation with disease severity. The blood level of expression of miR-34c, miR-132, miR-7, and miR-17 showed downregulation in the mild stage of PD compared the reference group and higher in the severe stages of the disease compared the mild stages of PD. Additionally, a significant upregulation of miR-181a was observed in the early onset of PD patients compared with the reference group. mir-132, miR7, and miR-29c showed a noteworthy downregulation in the early onset compared tothe control group. miR-7 and miR-29c showed a satisfactory value of AUC = (0.764, 0.745) to discriminate between individuals with PD and the reference control group; moreover, miR-132 reported a significant AUC = 0.816 to differentiate between PD patients and the control group, which suggests it can potentially be used as a blood biomarker. In addition, the seven miRNAs were linked to known PD pathways, and candidate-related target genes were presented.in-silico analysis identified candidate target genes and TFs, including those related to neurodegeneration and PD.